Kehidupan Anak Panti Asuhan Aisyiyah 1998–2024. - Dedi Asmara; Nahdatul Hazmi; Destel Meri; Chandra Dede (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The purpose of this study was to examine the lives of children in the ‘Aisyiyah orphanage in Payakumbuh City during the period 1998–2024, focusing on the social, economic, educational, and care dynamics within the institution. This research employed historical methods, including heuristics, source criticism, interpretation, and historiography, utilizing written sources, archives, and interviews. The results of this study indicate that the orphanage plays a crucial role in providing Islamic-based care, encompassing basic needs, formal and non-formal education, moral development, and life skills training. Since the Reformation Era, the institution has experienced gradual infrastructure improvements, although it continues to face challenges such as limited funding and a shortage of professional caregivers. Most children enter the orphanage due to poverty, the loss of one or both parents, or unfavorable family circumstances. The adaptation process for newcomers is often emotionally challenging, but a supportive, family-like environment and structured guidance help them grow and develop. Furthermore, this study shows that the transition of children leaving the orphanage to independence is supported through skills training programs, alumni networks, and local government assistance. Despite financial and facility constraints, the 'Aisyiyah Orphanage has survived and adapted to changing times, remaining a vital social institution contributing to the well-being of children in Payakumbuh City. The conclusion of this study is that the 'Aisyiyah Orphanage in Payakumbuh City has succeeded in becoming a pillar of protection and care for vulnerable children through a consistent Islamic and family approach. The success of its independence program and institutional adaptation proves its existence and real contribution in addressing social welfare problems in Payakumbuh City. Keywords: Aisyiyah, Child Care, Orphanage.